Alopecia areata totalis and universalis: a multicenter review of 132 patients in Spain. (6th October 2016) - Vañó‐Galván, S.; Fernández‐Crehuet, P.; Grimalt, R.; Garcia‐Hernandez, M.J.; Rodrigues‐Barata, R.; Arias‐Santiago, S.; Molina‐Ruiz, A.; Garcia‐Lora, E.; Dominguez‐Cruz, J.; Brugues, A.; Ferrando, J.; Serrano‐Falcón, C.; et al.
Abstract: Background: Alopecia areata totalis (AAT) and universalis (AAU) pose a therapeutic challenge. Objective: To describe the clinical and epidemiological features, therapeutic response and prognostic factors in a large series of patients diagnosed with AAT and AAU. Methods: This retrospective multicenter study included patients diagnosed with AAT/AAU with a minimum follow‐up of 12 months. Response was assessed based on the regrowth of scalp hair. Results: In all, 132 patients (92 women and 40 men) – 80 (61%) diagnosed with AAU and 52 (39%) diagnosed with AAT – were included. The median time between the presentation of alopecia areata (AA) and the development of extensive AA was 1 year and it was less than 4 years in 121 patients (91%). There was an initial response to treatment in 64% of patients, although only 14% presented a persistent response. Adverse side effects from the medications used were detected in 33% of patients. The prognostic factors associated with poor response were the presence of AAU and a positive family history of AA. Conclusions: Treatment of AAT and AAU is challenging. Although an initial regrowth may be achieved, the duration of response is usually short. There were no significant differences on the effectiveness or duration of response between the various systemic therapies.